2005
DOI: 10.1051/m2an:2005052
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of time-scheduled regimen for anti-cancer drug infusion

Abstract: Abstract. The chronotherapy concept takes advantage of the circadian rhythm of cells physiology in maximising a treatment efficacy on its target while minimising its toxicity on healthy organs. The object of the present paper is to investigate mathematically and numerically optimal strategies in cancer chronotherapy. To this end a mathematical model describing the time evolution of efficiency and toxicity of an oxaliplatin anti-tumour treatment has been derived. We then applied an optimal control technique to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…The Gompertz model was initially developed in the context of insurance [62] and was first used in the nineties to fit experimental data of tumour growth [81]. A lot of studies on drug control are based on these models [14,15,35,96,97,98,106,107,108]. For instance, Murray [106,107] considered a two-population Gompertz growth model with a loss term to model the effect of the cytotoxic drug.…”
Section: Ode Models For Growing Cell Populations With Drug Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gompertz model was initially developed in the context of insurance [62] and was first used in the nineties to fit experimental data of tumour growth [81]. A lot of studies on drug control are based on these models [14,15,35,96,97,98,106,107,108]. For instance, Murray [106,107] considered a two-population Gompertz growth model with a loss term to model the effect of the cytotoxic drug.…”
Section: Ode Models For Growing Cell Populations With Drug Controlmentioning
confidence: 99%
“…More recently, one of us and his co-workers [15,35] investigated the effects of oxaliplatin on tumour cells and healthy cells. To model tumour growth, they used a Gompertz model modified by a "therapeutic efficacy term" as a death term depending on the drug concentration.…”
Section: Ode Models For Growing Cell Populations With Drug Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…A L 2 or L 1 average is not very satisfying to consider because it does not exclude hectic behaviour (peaks and troughs) of the tumour cell population that is seldom in accordance with clinical observations. I proposed with C. Basdevant, see [20], to use minimisation of either the absolute minimal tumour cell number (if zero can be reached, then the tumour is eradicated); or the maximal tumour cell number within a given time interval, in the perspective of renewed chemotherapy courses. In the latter case, if this maximal number can be kept below a clinically tolerable threshold, compatible with survival with a good quality of life even if the tumour has not been eradicated, then the treatment may also be considered as successful.…”
Section: Defining Optimal Therapeutic Strategies Adapted To Differentmentioning
confidence: 99%
“…For instance, in a feasibility study reported in [20,53], a jejunal toxicity limit has been chosen, for it had been shown that in mice (the model parameters had been identified in mice) the jejunum was the most important toxicity target for the drug considered there, oxaliplatin. But it is more frequent to study toxicity effects on the haemotologic bone marrow, as has been done in a few studies with clinical applications [130,131,216].…”
Section: Limiting Toxic Side-effectsmentioning
confidence: 99%